2019
DOI: 10.1515/sjecr-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sociodemographic Factors on the Patient Satisfaction with Health Care System

Abstract: The goal of this paper is to determine the level of patient satisfaction with health care among adults in the Republic of Serbia and to analyze the correlation between the satisfaction and socio-demographic characteristics of the interviewees. The paper is based on the data provided by the National health survey of the Republic of Serbia. For the purposes of this paper, we used data on age and household of the people aged 19 and more. By eliminating the interviewees who were neither satisfied nor dissatisfied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The present study showed that married patients were most satisfied though not significant ( x  = 3.09, p < 0.05). Which is in agreement with findings of Sharifi, et al, (2012); Odetola (2015), Djordjevic and Vasiljevic, (2017); Karaca and Durna, (2019);and Okeke, et al, (2019); who reported more satisfaction among married people. While Garba et al, (2018) and Devi, et al (2020) found marital status not significantly associated with satisfaction status.…”
Section: Association Of Patients' Satisfaction and Socio-demographic supporting
confidence: 92%
“…The present study showed that married patients were most satisfied though not significant ( x  = 3.09, p < 0.05). Which is in agreement with findings of Sharifi, et al, (2012); Odetola (2015), Djordjevic and Vasiljevic, (2017); Karaca and Durna, (2019);and Okeke, et al, (2019); who reported more satisfaction among married people. While Garba et al, (2018) and Devi, et al (2020) found marital status not significantly associated with satisfaction status.…”
Section: Association Of Patients' Satisfaction and Socio-demographic supporting
confidence: 92%
“…The association between religious belief of an individual and her satisfaction with healthcare has been documented in previous studies. 23,24 Unlike that by Osiya et al, 23 women who were Christians were over 16 times more likely than the Moslems to be satisfied with the antenatal services received. A possible reason for this finding may be because the facilities studied were Christian missions with more inclinations towards Christian practices.…”
Section: Discussionmentioning
confidence: 82%
“…The relationship between satisfaction and socio-demographic/economic factors was reported by other studies elsewere. 36,37 The study finding also indicated a significant association between service characteristics (length of waiting time to see a provider) and women's satisfaction with screening services. Women who perceived waiting time as "medium" were nearly three times more likely to be satisfied than women who perceived waiting time as "long".…”
mentioning
confidence: 75%